MENELISIK HAK-HAK PEREMPUAN - Lathifah Munawaroh; Suryani Suryani (Kafa`ah: Journal of Gender Studies, 2020)
This paper analyzes women's rights in the thematic interpreter of Surat al-Nisā’. One of the surahs of the Qur'an which uses the name al-Nisā' and is enshrined by Allah as one of the Surahs of the Qur'an. Surat al-Nisā' means “the women” is a form how Islam respect to women.  The name of this surah is “the Women” because the discussions about womanhood are more discussed in this surah than in other surahs. The thematic interpretation of this surah is so important, because this surah is targeting the issues of women who are usually regarded as the marginalized part. The method used is to use a thematic interpretation method, as one form of contemporary interpretation method with the use of classical references such as the books of Tafsīr bil Ma'tsūr about Sura al-Nisā'. The results of this study explain that there are many rights related to women in Surat al-Nisā': equality rights with men are a central issue in this surah. In addition, there are other women’s rights: the right to choose a spouse and the right to inherit and fair treatment. These rights were existed long ago in the beginning of Islam, at a time when women's rights were castrated, not even seen as noble creatures when compared to men.